Enhanced Gruneisen Parameter in Supercooled Water - Gomes, Gabriel O.; Stanley, H. Eugene; Souza, Mariano de [UNESP] (Nature Publishing Group, 2019)
We use the recently-proposed compressible cell Ising-like model to estimate the ratio between thermal expansivity and specific heat (the Gruneisen parameter Gamma(s)) in supercooled water. Near the critical pressure and temperature, Gamma(s) becomes significantly sensitive to thermal fluctuations of the order-parameter, a characteristic behavior of pressure-induced critical points. Such enhancement of Gamma(s) indicates that two energy scales are governing the system, namely the coexistence of high- and low-density liquids, which become indistinguishable at the critical point in the supercooled phase. The temperature dependence of the compressibility, sound velocity and pseudo-Gruneisen parameter Gamma(w) are also reported. Our findings support the proposed liquid-liquid critical point in supercooled water in the No-Man's Land regime, and indicates possible applications of this model to other systems. In particular, an application of the model to the qualitative behavior of the Ising-like nematic phase in Fe-based superconductors is also presented.